1998
DOI: 10.1016/s0895-7061(98)00157-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in blood pressure and heart rate variability during dental surgery

Abstract: The objective of the present study was to determine the changes in blood pressure, pulse rate, and heart rate variability during dental surgery. The study included 40 patients, 19 to 74 years of age (mean age: 42.7+/-3.0 years), who underwent tooth extraction at our hospital. Holter electrocardiographic monitoring was used to determine the power spectrum of R-R variability before and during dental surgery. The low frequency (LF: 0.041 to 0.140 Hz), high frequency (HF: 0.140 to 0.500 Hz), and total spectral pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
11

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 12 publications
5
44
0
11
Order By: Relevance
“…Regarding age, in a study by Matsumura et al (16), patients in middle and advanced age had a greater increase in SP and DP during molar extractions than younger patients. In agreement with these authors, Nagao et al (17), in dental implant surgery under local anesthesia, showed that SP increased with age.…”
Section: Resultsmentioning
confidence: 95%
“…Regarding age, in a study by Matsumura et al (16), patients in middle and advanced age had a greater increase in SP and DP during molar extractions than younger patients. In agreement with these authors, Nagao et al (17), in dental implant surgery under local anesthesia, showed that SP increased with age.…”
Section: Resultsmentioning
confidence: 95%
“…Therefore since our study group consisted of a young group of patients with a mean age of 24, this may be the reason why there is a lack of significance in blood pressure and heart rate changes [24].…”
Section: Discussionmentioning
confidence: 99%
“…Cold Pressure Placement of ice wrapped in wet cloth on subject's forehead for 2 min. Hand in 4 • C water for 1 min [102,103] Mental Arithmetic Counting backwards from 500 in intervals of 7, Continuous addition of 3 digit numbers for 2 min [104] Relaxation Slow breathing/Meditative music [105,106] Amyl Nitrate Inhalation of vasodilator [107] Anesthesia Dental anesthesia [84,108] Isometric Exercise Raising legs/arms against pressure [109] Sustained Handgrip Clenching one's fist forcefully [110,111] Technologies 2017, 5, 21 10 of 19 inaccuracy of existing algorithms using PAT in tracking Low-Frequency (LF) variations in BP was one of the main reasons for inaccurate results [90,113]. In order to improve the accuracy, they introduced a factor termed "photoplethysmogram intensity ratio" (PIR), which could be determined by the ratio of the peak (Ip) and the foot (If) PPG values (Figure 3c).…”
Section: Comparison Between Modelsmentioning
confidence: 99%